PENGELOLAAN URUSAN PEMERINTAHAN BIDANG ENERGI DAN SUMBER DAYA MINERAL DI KABUPATEN SRAGEN - Kushandajani, Kushandajani (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The management of the Affairs of the administration of mineral resources and energy field is a very vital Affairs. Through an energy and mineral resources is subject to his life a lot of almost the entire population of Indonesia. In conjunction with the autonomous region, there is a division of duties and authorities delegated from the Centre and the province to the City/County is included in the management of energy and mineral resources. In the management of course there must be institutional authorities and get permission before carrying out exploration. The existence of an integrated one-stop permitting currently on the Government ease the Sragen district are expected to obtain permission in the management of energy and mineral resources. Based on the results of the research, it can be concluded that the institutional side of there is still overlap within the Division of duties and authorities between The SDA, DPU, BLH and BPTPM which resulted in complexity in the running tasks and authorities. the lack of qualified personnel resources in the field of energy and mineral resources, adding to the heavy workload that had to be in the way. In an effort to get permission apparently until recently there hasn't been good in terms of regulatory or permitting that specifically is an integrated one-stop licensing at BPTPM. This resulted in the applicant must be from table to table to get recommendations to the management of permissions. Therefore, it is necessary the presence of the Division of duties and authorities in detail through the applicable local regulations or Regent. Hiring employees with the competencies of the field of energy and mineral resources. As well as enforcing one-stop permitting at BPTPM in the management of mineral resources and energy with the help of a technical team consisting of SKPD related. Of course with such policies will support the Government in the framework of the management of Sragen district affairs governance areas such as energy and mineral resources.